1984
DOI: 10.1590/s0034-89101984000400009
|View full text |Cite
|
Sign up to set email alerts
|

Infecção experimental de Calomys callosus (Rodentia-Cricetidae) com Leishmania donovani chagasi (Laison, 1982)

Abstract: Foi descrita a infecção experimental em Calomys callosus com uma cepa de Leishmania donovani chagasi de caso humano. Um grupo de 22 roedores foi inoculado por via intraperitoneal com 0,1 ml de um macerado de baço em salina, rico em amastigotas. Esses animais foram sacrificados três meses após as inoculações, tendo sido realizado: cultura "in vitro" em meio acelular (LIT e NNN) e esfregaços, corados pelo Giemsa, de fígado, baço, medula óssea e sangue; cortes histológicos corados com hematoxilina-eosina de fígad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…callosus has also been experimentally infected with other parasites such as Schistosoma mansoni, Plasmodium berghei, Leishmania mexicana amazonensis, L. donovani chagasi, and Paracoccidio des brasiliensis (Borda 1972;Mello 1979;Mello and Teixeira 1984;Junqueira-Kipnis et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…callosus has also been experimentally infected with other parasites such as Schistosoma mansoni, Plasmodium berghei, Leishmania mexicana amazonensis, L. donovani chagasi, and Paracoccidio des brasiliensis (Borda 1972;Mello 1979;Mello and Teixeira 1984;Junqueira-Kipnis et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that mice and hamsters are still the most commonly used rodents as experimental animal models in leishmaniosis studies [ 62 , 63 , 64 , 65 ] and that there are few studies using C. callosus , here we demonstrate that C. callosus should be potentially used as an experimental model in leishmaniasis research [ 16 , 17 ].…”
Section: Leishmaniasismentioning
confidence: 75%
“…Experiments performed using Leishmania infantum , the etiological agent of VL, demonstrated that after 3 months of infection C. callosus presented hepato and splenomegaly, also parasite amastigote forms were found intra (macrophages) and extracellularly in the bone marrow, liver and spleen smears of infected rodents [ 17 ]. C. callosus could also be useful as an experimental animal model for VL, due to histopathological and visceral alterations promoted after infection.…”
Section: Leishmaniasismentioning
confidence: 99%
See 1 more Smart Citation
“…Após os primeiros estudos em laboratório, algumas espécies de roedores silvestres e sinantrópicos foram descritas como prováveis reservatórios de protozoários que causam LV em diferentes países (ADLER; THEODOR, 1931;MELO;TEIXEIRA, 1984;GRADONI et al, 1983;SVOBODAVÁ et al, 2003;BARBOSA, 2005). Na Grécia, Itália, Portugal e Venezuela, infecções naturais de Mus musculus, Rattus rattus, Rattus norvegicus e Sigmodon hispidus por L. donovani têm sido relatadas (BARI, 2006;LAINSON, 2010;PAPADOGIANNAKIS et al, 2009;HELHAZAR et al, 2013).…”
Section: Leishmaniose Visceral Em Roedoresunclassified